PEMBERIAN UMPAN BALIK PADA MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA KONSEP PEREDARAN DARAH PADA SISWA SD - Evi Ristiana (Universitas Muhammadiyah Makassar, 2018)
Penelitian ini merupakan penelitian tindakan kelas (class action research) yang bertujuan untuk meningkatkan hasil belajar melalui pemberian umpan balik pada model pembelajaran kooperatif tipe STAD (Student Team Achievement Division) siswa pada konsep Sistem Peredaran Darah. Subyek penelitian ini adalah siswa Kelas V SD Negeri 1 Mapilli Kabupaten Polewali-Mandar yang terdiri atas dua kelas. Penentuan subyek penelitian dilakukan secara langsung. Penelitian ini dilaksanakan dalam 2 siklus. Data diperoleh dengan menggunakan instrument penelitian yaitu test pilihan ganda yang dilaksanakan setelah empat kali pertemuan. Data dianalisis dengan menggunakan statistik deskriptif dan statistik infernsial dengan uji–t. Dari hasil analisis statistik deskriptif diperoleh nilai rata-rata hasil belajar siswa yang diajar dengan menggunakan model kooperatif STAD dengan umpan balik meningkat pada siklus II dengan nilai rata-rata 7,7 sedangkan pada siklus 1 lebih rendah dengan nilai rata-rata 6,5. Sedangkan hasil analisis statistik infernsial diperoleh nilai thitung = 10,91 ttabel = 1,96. Sehingga disimpulkan ada peningkatan hasil belajar melalui pemberian umpan balik pada model pembelajaran kooperatif tipe STAD siswa.This research is a class action research that aims to improve learning outcomes through the provision of feedback on the model of cooperative learning type STAD (Student Team Achievement Division) students on the concept of Circulatory Systems. The subjects of this study were students of Class V SD Negeri 1 Mapilli Polewali-Mandar Regency consisting of two classes. Determination of research subject is done directly. This study was conducted in 2 cycles. Data were obtained by using research instrument that is multiple choice test which was conducted after four meetings. Data were analyzed by using descriptive statistic and infernal statistic with t-test. From the results of descriptive statistical analysis obtained the average value of student learning outcomes are taught by using the STAD cooperative model with feedback increased in cycle II with an average value of 7.7 while in the 1st cycle lower with an average value of 6.5. While the result of statistical analysis infernsial obtained tcount = 10,91 ttable = 1,96. So it is concluded there is an increase in learning outcomes through the provision of feedback on the model of cooperative learning type STAD students.This research is a class action research that aims to improve learning outcomes through the provision of feedback on the model of cooperative learning type STAD (Student Team Achievement Division) students on the concept of Circulatory Systems. The subjects of this study were students of Class V SD Negeri 1 Mapilli Polewali-Mandar Regency consisting of two classes. Determination of research subject is done directly. This study was conducted in 2 cycles. Data were obtained by using research instrument that is multiple choice test which was conducted after four meetings. Data were analyzed by using descriptive statistic and infernal statistic with t-test. From the results of descriptive statistical analysis obtained the average value of student learning outcomes are taught by using the STAD cooperative model with feedback increased in cycle II with an average value of 7.7 while in the 1st cycle lower with an average value of 6.5. While the result of statistical analysis infernsial obtained tcount = 10,91 ttable = 1,96. So it is concluded there is an increase in learning outcomes through the provision of feedback on the model of cooperative learning type STAD students.